In’ikās al-Bī`ah fī al-Amṡāl al-‘Arabiyyah wa al-Malāiwiyyah - Farah Hanim Mohd Esa; Adham Hamawiya (IAIN Salatiga, 2021)
This study aimed to determine the environmental opposites between Arabic and Malay proverbs. It used contrastive descriptive method to analyze similarities and differences in environmental opposites of both proverbs. The data sources used were Arabic and Malay proverbs from various literatures. The results showed that in Malay proverbs, although the stories and events are lost, the words do not deviate far from general proverbs and particularly Arabic proverbs. Arabic and Malay proverbs environments have similar characteristics even though they use quite different word choices.